Butyrate attenuates lipolysis in adipocytes co-cultured with macrophages through non-prostaglandin E2–mediated and prostaglandin E2–mediated pathways. Issue 1 (December 2016) - Ohira, Hideo; Tsutsui, Wao; Mamoto, Rie; Yamaguchi, Sayaka; Nishida, Masako; Ito, Miki; Fujioka, Yoshio
Abstract Background Interactions between adipocytes and macrophages are associated with metabolic disorders. Production of pro-inflammatory mediators and the release of free fatty acids (FFAs) increase when these cells are co-cultured; butyrate significantly diminishes these effects by suppressing both the macrophage inflammatory and adipocyte lipolysis pathways. Butyrate is known to up-regulate the expression of prostaglandin E2 (PGE2). Therefore, we hypothesized that PGE2 is associated with the suppression of lipolysis by butyrate in co-culture. Methods Using contact or transwell co-culture methods with differentiated 3T3-L1 adipocytes and RAW264.7 macrophages, we investigated the effects of butyrate on the release of PGE2 into the medium and on lipolysis in adipocytes. To elucidate the underlying mechanism, we examined the effects of butyrate on cyclooxygenase-2 (COX2) and phospholipase A2 (PLA2) in co-cultured cells, and cyclic adenine monophosphate (cAMP) and protein kinase A type 1-α regulatory subunit (PRKAR1A) in co-cultured adipocytes. Silent interfering (si)RNA targeting of G-protein–coupled receptor (GPR)41 and 109A was employed to examine the effect on lipolysis in TNF-α–stimulated adipocytes. Results Co-culture increased PGE2 release into the medium, compared with cells cultured separately. Butyrate significantly increased PGE2 production. Co-culture elevated COX2 expression in macrophages and adipocytes, and butyrate further enhanced this effect. Co-culture enhanced cytosolic PLA2 activity in macrophages, which was further enhanced by butyrate. As for lipolysis, co-culture increased the release of FFAs and free glycerol into the medium, whereas butyrate (and to a lesser extent, PGE2) suppressed FFAs and free glycerol release. An inhibition study using a prostaglandin E receptor 3–selective antagonist suggested that approximately 40% of the suppressive effect of butyrate depends on the PGE2-mediated pathway, whereas 60% depends on a non-PGE2–mediated pathway. Co-culture increased cAMP and PRKAR1A levels in adipocytes, whereas butyrate restored the levels to those of the control. Similarly, in TNF-α–stimulated adipocytes, butyrate reduced FFAs and free glycerol release. siRNA inhibition of GPR41 and GPR109A suggested that the GPR109A-mediated pathway predominates, but the GPR41-mediated pathway also regulates the effect of butyrate on lipolysis in TNF-α–stimulated 3T3-L1 cells. Conclusions Butyrate attenuates lipolysis in adipocytes co-cultured with macrophages via non-PGE2–mediated and PGE2-mediated pathways.